Heavy Alcohol Exposure Activates Astroglial Hemichannels and Pannexons in the Hippocampus of Adolescent Rats: Effects on Neuroinflammation and Astrocyte Arborization - Gómez, Gonzalo I.; Falcon, Romina V.; Maturana, Carola J.; Labra, Valeria C.; Salgado, Nicole; Rojas, Consuelo A.; Oyarzun, Juan E.; Cerpa, Waldo; Quintanilla, Rodrigo A.; Orellana, Juan A. (Frontiers in Cellular Neuroscience, 2018)
A mounting body of evidence indicates that adolescents are specially more susceptible to alcohol influence than adults. However, the mechanisms underlying this phenomenon remain poorly understood. Astrocyte-mediated gliotransmission is crucial for hippocampal plasticity and recently, the opening of hemichannels and pannexons has been found to participate in both processes. Here, we evaluated whether adolescent rats exposed to ethanol exhibit changes in the activity of astrocyte hemichannels and pannexons in the hippocampus, as well as alterations in astrocyte arborization and cytokine levels. Adolescent rats were subjected to ethanol (3.0 g/kg) for two successive days at 48-h periods over 14 days. The opening of hemichannels and pannexons was examined in hippocampal slices by dye uptake, whereas hippocampal cytokine levels and astroglial arborization were determined by ELISA and Sholl analysis, respectively. We found that adolescent ethanol exposure increased the opening of connexin 43 (Cx43) hemichannels and pannexin-1 (Panx1) in astrocytes. Blockade of p38MAP kinase, iNOS and COXs, as well as chelation of intracellular Ca2+, drastically reduced the ethanol-induced channel opening in astrocytes. Importantly, ethanol-induced Cx43 hemichannel and Panx1 channel activity was correlated with increased levels of IL-1β, TNF-α, IL-6 in the hippocampus, as well as with profound alterations in astrocyte arbor complexity. Thus, we propose that uncontrolled opening of astrocyte hemichannels and pannexons may contribute not only to the glial dysfunction and neurotoxicity caused by adolescent alcohol consumption, but also to the pathogenesis of alcohol use disorders in the adulthood.